The Role of Sexual Self-Control as Moderator between Sexual Desire and Premarital Sexual Behaviors - Chindy Kencana Sari; Marselius Sampe Tondok; Darmawan Muttaqin (Jurnal Psikologi, 2020)
Sexual desire can be one of the antecedents for individual premarital sexual behavior. Otherwise, sexual self-control can prevent individuals from engaging premarital sexual behavior. This study aimed to examine the role of self-control in moderating the relationship between sexual desire and premarital sexual behavior. This study involved 209 emerging adults (18-25 years old) who were dating and not undergoing a long-distance relationship. The current study used Premarital Sexual Permissiveness measurement, dyadic sexual desire subscale from Sexual Desire Inventory-II, general sex-drive and stimulus-elicited sex-drive subscales from Perceived Sexual Control to measure premarital sexual behavior, sexual desire, and sexual self-control respectively. Results of regression analysis showed that sexual self-control did not moderate the relationship between sexual desire and kissing (∆R2 = 0.006, p > 0.05), as well as sexual desire and petting (∆R2 = 0.001, p > 0.05). However, self-control could be a moderator in the relationship between sexual desire and intercourse (∆R2 = 0.027, p < 0.01).